Evaluation of Rheological Behavior of Bitumen Modified with Nano Copper Oxide - H. Shafabakhsh, G.; R.Sajadib, S.; ., . (International Journal of Engineering and Technology, 2018)
Nowadays, one of the most challenging problems facing civil and transportation engineers, which consumes plenty of budgets (causes large amount of cost) for maintenance of asphalt roads, is asphalt destructions. Lots of efforts are done in order to increase the resistance and life span of asphalt, including development of bitumen properties. Bitumen is used broadly in road construction due to its appropriate properties; however, it has some major deficiencies which may lead to destructions of asphalt pavements. Therefore different bitumen modifications are implemented to achieve desired properties for different objectives, including (Such as) using rubber powder, waste materials, various polymers, etc. Recently, researchers are turning to nanotechnology to improve bitumen properties. Conducted studies on this topic (conducted research in this field) show that using modified bitumen by nanomaterial, increases the capacity of the pavementâ€™s load bearing and decreases probable cracks due to fatigue during the operation life of the pavement. In this study, Nano Copper Oxide is used to develop rheological properties of bitumen. Nanoparticles have been added to bitumen with amount of 2.5, 3 and 5 percent and then Dynamic Shear Rheometer (DSR) and Bending Beam Rheometer (BBR) experiments have been conducted to investigate the effects of using nanoparticles in pure bitumen. Results show that adding Copper Oxide nanoparticles to bitumen improves the performance of base bitumen, especially at middle and low temperatures.Â